Rotational Velocities and Radii Estimates of Low-mass Pre-main-sequence Stars in NGC 2264 - Laurin M. Gray; Katherine L. Rhode; Catrina M. Hamilton-Drager; Tiffany Picard; Luisa M. Rebull (The Astrophysical Journal)
Investigating the angular momentum evolution of pre-main-sequence (PMS) stars provides important insight into the interactions between Sun-like stars and their protoplanetary disks, and the timescales that govern disk dissipation and planet formation. We present projected rotational velocities ( v sin i values) of 254 T Tauri stars (TTSs) in the ∼3 Myr old open cluster NGC 2264, measured using high-dispersion spectra from the WIYN 3.5 m telescope’s Hydra instrument. We combine these with literature values of temperature, rotation period, luminosity, disk classification, and binarity. We find some evidence that weak-lined TTSs may rotate faster than their classical TTS counterparts and that stars in binary systems may rotate faster than single stars. We also combine our v sin i measurements with rotation period to estimate the projected stellar radii of our sample stars, and then use a maximum likelihood modeling technique to compare our radii estimates to predicted values from stellar evolution models. We find that starspot-free models tend to underestimate the radii of the PMS stars at the age of the cluster, while models that incorporate starspots are more successful. We also observe a mass dependence in the degree of radius inflation, which may be a result of differences in the birth-line location on the HR diagram. Our study of NGC 2264 serves as a pilot study for analysis methods to be applied to four other clusters ranging in age from 1−14 Myr, which is the timescale over which protoplanetary disks dissipate and planetary systems begin to form.